Cross-Species Gene Expression Analysis Reveals Gene Modules Implicated in Human Osteosarcoma - Jin, Zheng; Liu, Shanshan; Zhu, Pei; Tang, Mengyan; Wang, Yuanxin; Tian, Yuan; Li, Dong; Zhu, Xun; Yan, Dongmei; Zhu, Zhenhua (Frontiers in Genetics, 2019)
Background: Osteosarcoma (OS) is one of the malignant bone tumors occurring in both human and canine, and in both of them, it is characterized by a high rate of metastasis and poor prognosis. Cross-species analysis reveals previously neglected molecular or signaling pathways involved in the progression of diseases and dogs are genetically comparable to humans and live in similar environments. Therefore, the aim of this study was to find out OS hub genes through a cross-species analysis. Materials & Methods: All the human and canine OS gene expression data obtained by the Affymetrix platform were collected. After quality assessment and normalization, co-expression network was performed using weight gene co-expression network analysis (WGCNA). Species specific modules and consensus modules were identified. Protein-protein interaction (PPI) networks analysis was performed based on consensus gene modules. Then, consensus modules were functionally annotated and correlated with clinical traits. Hub nodes were identified by a subnetwork analysis of PPI network and WGCNA module membership. Modules of interest and hub nodes were validated in an external dataset. Results: Three modules for the human network, 7 modules for the canine network and 4 consensus modules were identified. The consensus module 3 (C3) showed a significant correlation with the metastatic status in the training dataset and a significant correlation with metastasis free survival in the external dataset. Cluster of differentiation 86 (CD86) was identified as the hub gene of C3, showing a significant correlation with metastasis free survival. Conclusion: Genes in C3 play an important role in OS metastasis, while CD86 might be a potential molecular biomarker for OS metastasis.